Marketing of Green Product in Indonesia Context Today - Arafah, Willy (British Journal of Marketing Studies, 2018)
This study aims to determine the extent to which consumer awareness of the environment either directly or indirectly currently exist in Indonesia, there are several companies that serve as unit of analysis in this study that has implemented the company go green, among others are: (1). The Body Shop, (2). PT. Unilever Indonesia Tbk, (3). NSN Indonesia, (4). Sofyan Hotel. In this study researchers want to know how much influence of green perceived value and green perceived risk against green purchased intention mediated by green trust to consumers who consume green products in Indonesia. The model in this study is to test the hypothesis of the research by distributing questionnaires as many as 459 questionnaires to consumers who have consumed green products for the last year in all areas of Jakarta, so the sampling technique is purposive random sampling and analysis data method in this research was using PLS (Partial Least Square) Method. The result of data processing in this research shows the influence, among others: (1). green perceived value has a positive effect on green trust of 0.876; (2). green perceived risk has a negative effect on green trust of -0.445; (3). green trust has a positive influence on green purchased intention sebeesar 0.11; (4). green perceived value has a direct effect of 0.650 to green purchase intention: (5). green perceived risk has a negative effect on green purchase intentuio of -0.22 but not significant. So in this study it can be concluded that consumers who consume green products are strongly influenced by green perceived value but will have greater influence if mediated by green trust, so producers who produce green products must create value for consumers so that will create consumer loyalty in long term.